Efeitos de histórias experimentais e de esquemas de reforço sobre o seguir regras - OLIVEIRA, Valdete Leal de (2014)
In an investigation of variables that may interfere with rule-following, 16 college students were exposed to a matching-to-sample procedure, where they had to point, in sequence, to three comparison stimuli. Baseline was referred in Phase 1. In Phase 2, the correct sequence was established by contingencies, and in Phase 3 the discrepant rule to contingencies was presented. The reinforcement schedules in Phases 2 and 3 were manipulated as follows: For Groups 1 and 2, a CRF schedule was used in Phase 2 and also in Phase 3 of Group 1; schedule FR3 was employed in Phase 3 of Group 2. For Groups 3 and 4, the schedules were FR3 in Phase 2, FR3 in Phase 3 of Group 3, and CRF in Phase 3 of Group 4. The history constructed in Phase 2, as well as the schedule in Phase 3, interfered with rule-following.